2006
DOI: 10.1128/jcm.00447-06
|View full text |Cite
|
Sign up to set email alerts
|

Spread of Escherichia coli Strains with High-Level Cefotaxime and Ceftazidime Resistance between the Community, Long-Term Care Facilities, and Hospital Institutions

Abstract: A total of 151 Escherichia coli strains resistant to cefotaxime and ceftazidime were isolated during a prospective surveillance study. These strains were characterized by clinical, microbiological, and molecular analyses and were distributed into four clusters of 103, 11, 6, and 5 isolates, along with 25 unrelated strains. The principal cluster was isolated from urine, wound, blood, and other samples in three hospitals, eight nursing homes, and a community healthcare center. This cluster was associated with bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
107
3
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(128 citation statements)
references
References 30 publications
11
107
3
4
Order By: Relevance
“…Downstream of four out of six bla CTX-M-14 genes (14, 12, 8, and 21), an IS903-like element was found as already described for this gene (24). ISEcp1 was not identified upstream of the bla CTX-M-2 and bla CTX-M-9 genes, as previously reported (21). ISCR1 was found in isolates harboring bla CTX-M-2 and bla CTX-M-9 genes (Fig.…”
Section: Epidemiology and Pcr Detection Of ␤-Lactamase Genessupporting
confidence: 64%
See 1 more Smart Citation
“…Downstream of four out of six bla CTX-M-14 genes (14, 12, 8, and 21), an IS903-like element was found as already described for this gene (24). ISEcp1 was not identified upstream of the bla CTX-M-2 and bla CTX-M-9 genes, as previously reported (21). ISCR1 was found in isolates harboring bla CTX-M-2 and bla CTX-M-9 genes (Fig.…”
Section: Epidemiology and Pcr Detection Of ␤-Lactamase Genessupporting
confidence: 64%
“…PFGE analysis showed that the spread of bla CTX-M -positive E. coli and K. pneumoniae isolates was not related to the spread of single clones as reported in several studies from other countries (United Kingdom, France, Italy, and Spain) (8,20,21,29).…”
Section: Discussionmentioning
confidence: 63%
“…The presence of bla CTX-M-15 has previously been associated with E. coli strains of phylogroups B2 and D, and in some instances, with specifi c PFGE types (9)(10)(11)(12)16). We detected an emerging and globally disseminated CTX-M-15 phylogroup B2 E. coli strain corresponding to the ST131 that was responsible for clonal outbreaks in Canada, France, Spain, and Portugal (11,14,16,23). Other CTX-M-15 B2 strains belong to clonal complexes ST695, ST405, ST354, or ST28, which have previously been detected in different geographic areas among isolates that do not express CTX-M-15 (online Appendix Figure, available from www.cdc.gov/EID/content/14/2/195-appG.htm).…”
Section: Discussionmentioning
confidence: 87%
“…Although the isolates in our study do not belong to clone CgA, they were isolated mainly from urine samples, and an association of ST131 E. coli isolates with urinary tract infections might be inferred. Although most CTX-M-15 isolates studied were recovered from hospitalized patients, these microorganisms are now widely spread in the community setting, including long-term care facilities in the countries from which isolates included in this study originated (2,5,14,33). Our study has increased knowledge of the number of epidemic E. coli clonal complexes causing urinary tract infections.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, yersiniabactin is disproportionately associated with antibiotic-resistant strains, including Ͼ90% of strains of the E. coli sequence type 131 (ST131), an alarming pandemic multidrug-resistant (MDR) clonal group (48)(49)(50)(51), and Ͼ60% of respiratory carbapenemase-producing K. pneumoniae strains, compared to 10% of susceptible K. pneumoniae strains (41). Novel antimicrobial agents or vaccines that target yersiniabactin iron transport or other pathogen-associated nutrient acquisition systems may provide an effective strategy to combat the rising surge of antibiotic-resistant common infections.…”
Section: Figmentioning
confidence: 99%